First evidence of the pig-nosed turtle (Carettochelys insculpta) vocalizing underwater - Ferrara, Camila Rudge; Vogt, Richard Carl; Eisemberg, Carla Camilo; Doody, Jean Sean (Copeia, 2017)
Recent research has demonstrated that some freshwater turtles vocalize underwater, but the taxonomic breadth of this mode of communication in freshwater turtles is unknown, hindering our understanding of its evolution. The Pig-nosed Turtle (Carettochelys insculpta), a monotypic genus inhabiting tropical Australia and New Guinea, is a likely candidate for producing underwater sounds because it exhibits social behavior while feeding, nesting, and thermoregulating. We tested the hypothesis that C. insculpta vocalizes using an omnidirectional hydrophone. We recorded C. insculpta emitting sounds underwater in the field and in captivity in northern Australia in May 2014. Analysis revealed that the 182 sounds produced by seven individuals could be separated into three sound categories. The sounds were simple and characteristic of a contact call, and were similar to those recently reported in other species of aquatic turtles. Further research should focus on the role of sound production in social activities. © 2017 by the American Society of Ichthyologists and Herpetologists.
Keywords: Bioacoustics; Communication Behavior; Freshwater Ecosystem; Social Behavior; Turtle; Underwater Environment; Underwater Noise; Vocalization; Australia; New Guinea; Carettochelys; Carettochelys Insculpta; Testudines